Value for Money Analysis of Zakat Institutions: Insights from Indonesia - Zakiy, Faris Shalahuddin; Falikhatun, Falikhatun (UIN Sunan Kudus, 2024)
This study aims to analyze the growth of collection and the effectiveness and operational efficiency of zakat institutions activities. To achieve this goal, this research uses qualitative methods with a content analysis approach. This study examines 9 zakat institutions in Indonesia for 3 years from 2019 to 2021 with 27 observations. Data analysis uses a value for money approach modified by Puskas BAZNAS. To measure effectiveness using the net allocation to collection ratio (NACR), while to measure efficiency using the operational costs ratio (OCR), human resource costs ratio (HRCR), and operational costs ratio of amil rights (OCRAR). This study found that there were quite significant fluctuations in the growth of zakat institutions in the last two years. This study also found that the average NACR at zakat institutions for the last three years was considered very effective. While the efficiency ratio measured using OCR, HRCR, OCRAR is considered efficient. The performance of zakat institutions in Indonesia from a value for money perspective can be said to be good.